Correlation analysis of serum FCAS1, Procalcitonin and SCYA25 levels with the prognosis of patients with sepsis: Serum FCAS1, Procalcitonin and SCYA25 levels in prognosis of sepsis - Yang, Yanhong; Hua, Yali; Yuan, Jing; Chen, Qingmei (Journal of Medical Biochemistry, 2026)
Objective To explore the levels of serum Familial Cold Autoinflammatory Syndrome 1 (FCAS1), Procalcitonin, and Small Inducible Cytokine A25 (SCYA25) in patients with sepsis caused by drug-resistant Klebsiella pneumoniae (KP) infection and their relationship with prognosis.Methods The study group consisted of 410 patients who were hospitalized to our hospital between March 2019 and March 2024 and had sepsis brought on by KP. A total of 196 drug-resistant patients with sepsis caused by KPs were classified into the drug-resistant group, and 214 nondrug-resistant patients with sepsis caused by KPs were classified into the nondrug-resistant group. According to the severity of sepsis, 410 patients with KP-induced sepsis were divided into a severe sepsis group (178 patients) and a sepsis group (232 patients). The control group consisted of an additional 410 healthy volunteers who were examined physically at our hospital throughout the same time period. It was established that drug-resistant KPs were resistant to clinical medications. The prognosis of patients with drug-resistant sepsis caused by a KP infection was split into a survival group and a death group 28 days after admission. Serum FCAS1 levels were detected via an enzyme-linked immunosorbent assay, and serum Procalcitonin and SCYA25 levels were determined via the chemiluminescence method. The diagnostic value of serum FCAS1, Procalcitonin, and SCYA25 for drug-resistant KP-induced sepsis as well as their predictive value for the mortality of patients with drug-resistant KP-induced sepsis were examined using receiver operating characteristic (ROC) curves. Multivariate logistic regression analysis was used to investigate the factors impacting death in patients with sepsis and drug-resistant KP infection.Results A total of 250 drug-resistant KP strains were detected in 196 patients with sepsis caused by drug-resistant KPs. The resistance rates of these strains to cefazoline, ceftriaxone, ceftazidime, amtronam, imipenem and meropenem were greater than 90%. Serum FCAS1, Procalcitonin, and SCYA25 levels exhibited a statistically significant difference (P
Keywords: Sepsis; Drug resistance; Klebsiella pneumoniae; Nucleotide-binding oligomerization domain-like receptor protein 3; Procalcitonin; Procalcitonin; Small Inducible Cytokine A25